Study of Identity Styles and Multiple Intelligences, and Their Relationship with the Quality of Working Life among Female Employees of Yazd University - Faezeh Forghani; Ahmad Zandvanian; Seyed Kazem Alavi Langroudy (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: One of the most important goals of organizations is to increase the quality of working life of employees and the most important part of employees of organizations are working women who, in addition to personal life responsibility, must have a relatively high quality of work life to be able to meet the goals satisfy the formation of organizations. The present study aims to investigate the situation of identity styles and multiple intelligence and their relationship with quality of working life of female employees at Yazd university in 2019. Method: This study is descriptive- survey in terms of data collection and pure in terms of purpose. The statistical population of this study consisted of 159 female employees of Yazd university which of 120 employees were selected based on the Krejcie and Morgan table by using simple random sampling method. The scales used to collect data were: Berzonskychr('39')s identity styles scale, Armstrongchr('39')s multiple intelligence scale, and Waltonchr('39')s work life quality questionnaire. The data were analyzed using pearson correlation coefficient, chi- square test, one- sample t- test, analysis of variance with repeated measures and bonferroni test. Results: The results showed that intrapersonal intelligence and normative identity style were more prevalent among female employees of Yazd university than other types of intelligence and identity style. Quality of working life was average and commitment among female employees was above average, as well as, no relationship was found between identity styles with quality of work life. Also among multiple intelligences, only rational- mathematical intelligence had a positive and significant relationship with quality of working life. Conclusion: It can be concluded that managers of organizations should strive to employ people with informational and normative identity styles, as well as, provide opportunities to utilize multiple intelligence of employees to increase the quality of working life in order to strengthen the productivity.